2004
DOI: 10.1111/j.1533-2500.2004.04003.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Lumbar Discectomy: Clinical Response in an Initial Cohort of Fifty Consecutive Patients With Chronic Radicular Pain

Abstract: STUDY OBJECTIVEThis paper reports on response to percutaneous discectomy in the initial cohort of 50 patients treated with the Dekompressor® 1.5 mm percutaneous lumbar discectomy probe at a 6-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 39 publications
1
52
0
Order By: Relevance
“…In his study, Alo used a Dekompressor 1.5 mm percutaneous discectomy probe to mechanically debulk the disc material, allowing for a reduction in intradiscal pressure. Although Alo et al used a different technology, they achieved the same goal as we did in our study using nucleoplasty 29. The mechanisms underlying the successes of both procedures are postulated to be related to disc remodeling, which results in volume reduction with a subsequent decrease in intradiscal pressure and a concomitant reduction in release of inflammatory mediators 30–32…”
Section: Discussionsupporting
confidence: 55%
“…In his study, Alo used a Dekompressor 1.5 mm percutaneous discectomy probe to mechanically debulk the disc material, allowing for a reduction in intradiscal pressure. Although Alo et al used a different technology, they achieved the same goal as we did in our study using nucleoplasty 29. The mechanisms underlying the successes of both procedures are postulated to be related to disc remodeling, which results in volume reduction with a subsequent decrease in intradiscal pressure and a concomitant reduction in release of inflammatory mediators 30–32…”
Section: Discussionsupporting
confidence: 55%
“…The fast-spinning inner cannula tip can aspirate the disc material into the tissuecollecting chamber and decrease the pressure inside the disc. 181 No study has yet reported whether this DeKompressor technique can obtain live disc cells because fastspinning inner cannula can generate heat and destroy disc cells. If the disc cell samples obtained through the DeKompressor can be alive, it may prove to be a useful tool for future research on disc cell culture, expansion, functional evaluation for matrix formation, and possible autologous transplantation to prevent and treat the discogenic pain due to disc degeneration and IDD.…”
Section: Cell Transplantationmentioning
confidence: 99%
“…This causes ''disc decompression'', reducing intradiscal pressure, and theoretically redistributing and alleviating the internal forces which cause irritation of the neighboring nerve root [1,8,39,48,53]. This is posited to downregulate local inflammatory mediators, reduce disc size, and initiate the healing process, all contributing to a reduction in discogenic pain [13].…”
Section: Introductionmentioning
confidence: 99%